Pattern of Asphyxial Deaths in Forensic Autopsies - Naseem Akhtar, Sono Mal, Azra Anwar, Aisha Rasheed, Ijaz Aziz, Ishtiaque Ali Langah (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To observe the pattern of the asphyxial deaths among the medicolegal autopsies. Study design: Prospective observational study Place and duration of study: Medicolegal Section, Liaquat University Hospital, Hyderabad from 1st January 2015 to 31st December 2019. Methodology: One hundred and forty seven autopsies were characterized as asphyxial. The data was obtained from forensic autopsy reports and was collected in a preformed data collection sheet after acquiring consent of close relatives. Results: There were 107 males and 40 females. Most of the subjects belonged to age group of adults (≥19 to <60 years) followed by age group of teens (13-18 years). The medicolegal autopsy was performed for 58 and 49 deceased from urban and rural areas, respectively. The asphyxial deaths were characterized as drowning (57.82%), hanging (16.32%), strangulation (14.28%), suffocation (8.16%), and throttling (3.40%). Conclusion: The drowning was the most common mechanism of asphyxia in medicolegal autopsies. The hanging also contributed substantial number in asphyxial deaths. Most types of asphyxia were higher in males of adult age than in females.